Reliability of Isokinetic Strength Assessments of Knee and Hip Using the Biodex System 4 Dynamometer and Associations With Functional Strength in Healthy Children - Vanessa van Tittelboom; Vanessa van Tittelboom; Ipek Alemdaroglu-Gürbüz; Britta Hanssen; Britta Hanssen; Lieve Heyrman; Hilde Feys; Kaat Desloovere; Patrick Calders; Christine Van den Broeck (Frontiers Media S.A., 2022)
BackgroundThis study aimed to analyze the reliability of concentric isokinetic strength assessments (knee and hip) using the Biodex System 4 in healthy children and assess the association with functional strength tests (sit-to-stand [STS], lateral-step-up [LSU]).Methods19 children (6-12 years) were included. Knee and hip flexion and extension, and hip abduction and adduction were tested at 60 and 90°/s.ResultsRelative and absolute reliability at 60°/s tended to show better results compared to those at 90°/s. Intra class correlations (ICCs) of knee flexion and extension at 60°/s were good (0.79-0.89). For hip flexion, extension, abduction and adduction at 60°/s ICCs were moderate to good (0.53-0.83). The smallest detectable change (SDC) values (expressed in %) were highly variable. The SDC% for knee flexion and extension and hip abduction at 60°/s were around 50%. Positive associations were found between hip extension and abduction isokinetic strength and the STS test.ConclusionConcentric isokinetic strength assessments in healthy children using the Biodex System 4 were found reliable for knee flexion and extension and hip abduction. Limited associations were found between concentric isokinetic strength tests and functional strength tests.